Solvent-dependent self-assembly of two dimensional layered perovskite (C6H5CH2CH2NH3)2MCl4 (M = Cu, Mn) thin films in ambient humidity - Garam Park (Nature Portfolio, 2018)
Abstract Two dimensional layered organic-inorganic halide perovskites offer a wide variety of novel functionality such as solar cell and optoelectronics and magnetism. Self-assembly of these materials using solution process (ex. spin coating) makes crystalline thin films synthesized at ambient environment. However, flexibility of organic layer also poses a structure stability issue in perovskite thin films against environment factors (ex. moisture). In this study, we investigate the effect of solvents and moisture on structure and property in the (C6H5(CH2)2NH3)2(Cu, Mn)Cl4 (Cu-PEA, Mn-PEA) perovskite thin films spin-coated on Si wafer using three solvents (H2O, MeOH, MeOH + H2O). A combination of x-ray diffraction (XRD) and x-ray absorption spectroscopy (XAS) show that relative humidity (RH) has a profound effect on perovskite thin films during sample synthesis and storage, depending on the kind of solvent used. The ones prepared using water (Cu-PEA:H2O, Mn-PEA:H2O) show quite different behavior from the other cases. According to time-dependent XRD, reversible crystalline-amorphous transition takes place depending on RH in the former cases, whereas the latter cases relatively remain stable. It also turns out from XAS that Mn-PEA thin films prepared with solvents such as MeOH and MeOH + H2O are disordered to the depth of about 4 nm from surface.